Analysis of trees planted in vicinity of hospitals in Ljubljana as a source of pollen - Kofol-Seliger, Andreja (Zbornik gozdarstva in lesarstva, 2010)
The paper analyses woody plants growing in the vicinity of hospital buildings situated along Zalog Road, Korytko Street, Šlajmar Street, Bohorič Street and Njegoš Street in Ljubljana, Slovenia. Woody plants are an immediate potential source of allergenic pollen, affecting all park users such as patients, visitors and hospital employees. The most allergenic tree species in the park was found to be birch (Betula pendula Roth.), which accounts for 6.8% of all registered trees. The low allergenic maples (Acer sp.) and the low allergenic horse chestnut (Aesculus hippocastanum L.) account for 19.6% and 7.4%, respectively. Among the medium allergenic trees are ash (Fraxinus excelsior L.) (4.8%), plane (Platanus x hispanica Muenchh.) (4.2%), hornbeam (Carpinus betulus L.) (1.9%), and oak (Quercus sp.) and hazel (Corylus avellana L.) withless than 1%.
Keywords: alergene rastline; bonišnice; drevesa; Ljubljana